From Histopathology to High-Resolution Ultrasound Imaging of Skin Scars - Vincenzo Ricci; Giulio Cocco; Danilo Donati; Giacomo Farì; Ke-Vin Chang; Levent Özçakar (Diagnostics, 2023)
Nowadays, modern ultrasound machines and high-frequency transducers allow us to accurately assess the superficial soft tissues of the human body. In this sense, sonographic evaluation of the skin and related pathologies is progressively growing in the pertinent literature. To the best of our knowledge, a standardized sonographic protocol focused on the assessment of pathological skin scars is still lacking. As such, the main purpose of the present study was to propose a technical guide to sonographically assess skin scars in the daily practice of clinicians—starting from knowledge on their histopathological features. In order to standardize the ultrasound examination, a superficial-to-deep, layer-by-layer approach has been proposed to optimize its reproducibility and to promote a common language among the different healthcare providers.